Progress in Stem Cells-Based Replacement Therapy for Retinal Pigment Epithelium: In Vitro Differentiation to In Vivo Delivery - Gupta, Santosh; Lytvynchuk, Lyubomyr; Ardan, Taras; Studenovska, Hana; Sharma, Ruchi; Faura, Georgina; Eide, Lars; Shanker Verma, Rama; Znaor, Ljubo; Erceg, Slaven; Stieger, Knut; Motlik, Jan; et al. (Stem cells translational medicine, 2023)
Retinal pigment epithelium (RPE) is a critical cell monolayer forming the blood-retina-barrier (BRB) and a permeable bridge between the choriocapillaris and the retina. RPE is also crucial in maintaining photoreceptor function and for completing the visual cycle. Loss of the RPE is associated with the development of degenerative diseases like age-related macular degeneration (AMD). To treat diseases like AMD, pluripotent stem cell-derived RPE (pRPE) has been recently explored extensively as a regenerative module. pRPE like other ectodermal tissues requires specific lineage differentiation and long-term in vitro culturing for maturation. Therefore, understanding the differentiation process of RPE could be useful for stem cell-based RPE derivation. Developing pRPE-based transplants and delivering them into the subretinal space is another aspect that has garnered interest in the last decade. In this review, we discuss the basic strategies currently employed for stem cell-based RPE derivation, their delivery, and recent clinical studies related to pRPE transplantation in patients. We have also discussed a few limitations with in vitro RPE culture and potential solutions to overcome such problems which can be helpful in developing functional RPE tissue.
Keywords: embryonic stem cells; retinal pigment epithelium; Macular Degeneration; Retina; induced pluripotent stem cells; differentiation; buněčná diferenciace; Cell Differentiation; Humans; Pluripotent Stem Cells; retinální pigmentový epitel; makulární degenerace; retina; Retinal Pigment Epithelium; cell delivery; pluripotentní kmenové buňky; lidé